SHORT TERM INDUCTION OF LPS DAMAGES THE HIPPOCAMPUS GYRUS THROUGH APOPTOSIS ON GLIAL CELLS MICE - Syifak, Shobihatus; Yuniati, Dyah; Hidayatullah, .; Salim, Hotimah Masdan (LIFE: International Journal of Health and Life-Sciences, 2021)
Sepsis is a condition that causes the highest mortality in the ICU. Sepsis occurs due to an infectious process that causes damage to organs such as the brain. During the sepsis process, the brain plays a full role in the body's defense, so that it manifests as encephalopathy. However, the mechanism in short-term sepsis not fully describes. This study aims to examine brain damage to the hippocampal gyrus in experimental animals induced by LPS in a short time. Methods: Mus musculus mice aged 8 weeks were divided into three groups namely control group (Ctrl), induction of LPS for 4 h (LPS-4h), and induction of LPS for 8 h (LPS-8h). LPS was injected by intraperitoneal with 25 mg/kg. The brain damage was seen histologically with HE staining. Results: The results of LPS injection showed an insignificant increase in leucocytes among all groups. Whereas the histological analysis found that glial cell damages increased significantly (P<0.05) with time dependency after LPS induction compared with the control group. Conclusion: Short-term induction of LPS destroys the hippocampal gyrus via high glial cells.